On the beneficial roles of fading and transmit diversity in wireless power transfer with nonlinear energy harvesting - Clerckx,B; Kim,J (IEEE Transactions on Wireless Communications, 2018)
We study the effect of channel fading in WirelessPower Transfer (WPT) and show that fading enhances the RF-to-DC conversion efficiency of nonlinear RF energy harvesters.We then develop a new form of signal design for WPT, denoted asTransmit Diversity, that relies on multiple dumb antennas at thetransmitter to induce fast fluctuations of the wireless channel.Those fluctuations boost the RF-to-DC conversion efficiencythanks to the energy harvester nonlinearity. In contrast with(energy) beamforming, Transmit Diversity does not rely onChannel State Information at the Transmitter (CSIT) and doesnot increase the average power at the energy harvester input,though it still enhances the overall end-to-end power transferefficiency. Transmit Diversity is also combined with recentlydeveloped (energy) waveform and modulation to provide furtherenhancements. The efficacy of the scheme is analyzed usingphysics-based and curve fitting-based nonlinear models of the en-ergy harvester and demonstrated using circuit simulations, pro-totyping and experimentation. Measurements with two transmitantennas reveal gains of 50% in harvested DC power over a singletransmit antenna setup. The work (again) highlights the crucialrole played by the harvester nonlinearity and demonstrates thatmultiple transmit antennas can be beneficial to WPT even in theabsence of CSIT.